The Death Instinct and Spiritual Culture - Govedarica, Milanko (Sociološki pregled, 2022)
This paper primarily elucidates various connotations of Freud‘s idea of the death instinct: striving to restore the inorganic condition, repetition compulsion, (self-)destructive behaviour and morality rigour. It further presents Scheler‘s critique of psychoanalysis and, in this context, it also explains the purpose of his definition of human‘s essence as an ascetic being and a bearer of spirituality. It notes certain similarities between Freud and Scheler, but it also expresses the position that it is not justifiable to reduce spiritual culture merely to psychoanalytical dynamics of the death instinct, it is not justifiable either to reduce it to a combination of self-destruction and erotic instincts. Theoretical and practical advantages of the presented position of this German philosopher are illustrated by an example of Frankl‘s logotherapy, by which it was influenced. Finally, it sheds light on the crucial point of Scheler‘s sociology of knowledge.
Keywords: death instinct; spirituality; psychoanalysis; logotherapy; sociology of knowledge